Developing Engaging Audio-Visual Learning Media for Basic Locomotor Patterns through Play-Based Activities for Early Learners - Arfi, Jeni; Wahyuri, Asep Sujana; Gusril, Gusril; Rasyid, Willadi; Ockta, Yovhandra (JETL (Journal of Education, Teaching and Learning), 2024)
This research aims to develop interactive learning media for physical education, sports and health, based on audio-visual, basic pattern motion materials based on games in elementary schools in Phase A. Based on the researcher's observation, there has been no development of audio-visual learning media at the Phase A level on locomotor motion materials, so the researcher tries to present learning media that is adapted to the Independent curriculum as a solution students who still have shortcomings, such as students' understanding of basic movement materials that are not optimal.  This type of research is Research and Development (R&D) using the ADDIE development model, which consists of 5 development steps, namely Analyze,  Design, Development, Implementation  and Evaluation. This research was assisted by 3 validators. The instrument used in this study is a validation sheet. The data analysis technique uses a scoring scale and a percentage range.From the research that has been carried out, it is found that the validity of the media developed has a percentage of 92.5% with a very feasible classification. Then for the student response, which is 97.92%, with that the audio-visual learning media in PE learning is a game-based basic locomotor movement pattern material at the phase A elementary school level.